IMPLEMENTASI PROGRAM BANTUAN LANGSUNG TUNAI DANA DESA BAGI MASYARAKAT MISKIN TERKENA DAMPAK COVID-19 : (Studi di Desa Moyo Mekar, Kecamatan Moyo Hilir, Kabupaten Sumbawa) - Kholiqin Auzanul; Gani Abdul Juli Andi; Wanusmawatie Ike (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2023)
The village Fund Direct Cash Assistance Program which has been established by the central governemnt in overcoming the economy of rural communities due to Covid-19 requires the village government to implement the program so that the process and benefits can be felt . The results of the study show that the process of implementing the Village Fund Direct Cash Assistance Program for the poor affected by Covid-19 in Moyo Mekar Village has fulfilled the success factors of program implementation according to George Edward III which mentions the existence of communication, resources, disposition and bureaucratic structure in the implementation process. The village government has communicated with all parties involved in the program implementation process such as communicating with village communities. There are adequateresources such as staff and infrastructure so that they cas assist the program implementation process. There is a disposition, namely the efforts made by the village government in overcoming the problems faced by program implemenres such as providing food and drink. Has been equipped with a clear bureaucratic structure to serve as operational standards in implementing the program. Besides that, the economic impact of the assistance is that it can meet community needs such as fulfilling food ingredients.